2002
DOI: 10.1128/ec.01.1.11-21.2002
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in the Eukaryotic Cell

Abstract: The major cellular pathways for protein and organelle turnover are autophagy and proteasome-mediated degradation. These processes are important to maintain a well-controlled balance between anabolism and catabolism in order to have normal cell growth and development. They play an essential role during starvation, cellular differentiation, cell death, and aging but also in preventing some types of cancer (59). These degradation pathways permit the cell to eliminate unwanted or unnecessary organelles and to recy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
410
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 513 publications
(420 citation statements)
references
References 140 publications
(297 reference statements)
8
410
0
2
Order By: Relevance
“…In mammalian cells three different main mechanisms contribute to the degradation of intracellular components inside lysosomes (autophagy) (Dice, 2000;Reggiori and Klionsky, 2002;Wang and Klionsky, 2003; Cuervo, 2004a,b microautophagy, result in the degradation of complete regions of the cytosol, including organelles, in the lysosomal lumen. Although degradation of organelles by these autophagic pathways can be selective (i.e., specific removal of damaged mitochondria sparing normal functioning ones) (Lemasters et al, 2002), there is no evidence supporting selectivity for the degradation of soluble cytosolic proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian cells three different main mechanisms contribute to the degradation of intracellular components inside lysosomes (autophagy) (Dice, 2000;Reggiori and Klionsky, 2002;Wang and Klionsky, 2003; Cuervo, 2004a,b microautophagy, result in the degradation of complete regions of the cytosol, including organelles, in the lysosomal lumen. Although degradation of organelles by these autophagic pathways can be selective (i.e., specific removal of damaged mitochondria sparing normal functioning ones) (Lemasters et al, 2002), there is no evidence supporting selectivity for the degradation of soluble cytosolic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cells three different main mechanisms contribute to the degradation of intracellular components inside lysosomes (autophagy) (Dice, 2000;Reggiori and Klionsky, 2002;Wang and Klionsky, 2003;Cuervo, 2004a,b). Two of those mechanisms, macroautophagy and Article published online ahead of print.…”
Section: Introductionmentioning
confidence: 99%
“…One process that cells use to respond to internal or external stress is autophagy. Autophagy is a degradative process responsible for the rapid degradation of damaged or unnecessary organelles and a large portion of the cytosol in the lysosome/vacuole lumen (Reggiori and Klionsky, 2002;Klionsky, 2004). In addition, autophagy is involved in cellular remodeling, development, and aging and also plays a role in preventing a range of diseases including some types of cancer and neurodegeneration (reviewed in Shintani and Klionsky, 2004;Levine and Klionsky, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is a major catabolic pathway in eukaryotic cells and is a vital pathway for degrading normal and aggregated proteins and altered or unwanted organelles, particularly under stress conditions [17] . Autophagy at an appropriate level not only plays a crucial role in protein quality control, but also acts as a defense response to stress, thus maintaining cellular homeostasis [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy at an appropriate level not only plays a crucial role in protein quality control, but also acts as a defense response to stress, thus maintaining cellular homeostasis [17] . Previous studies have demonstrated that Aβ is generated in Aβ precursor protein-rich organelles during autophagic turnover [18] .…”
Section: Introductionmentioning
confidence: 99%